KARYA TARI KOLABORASI RAMAYANA KONTEMPORER X SUB ORDINAT - Saputri, Bulan Noverina Rahma; Supriyanto, Eko (Greget: Jurnal Kreativitas dan Studi Tari, 2025)
The dance work “Sub-Ordinat” is a contemporary creation based on a Practice-led Research approach, exploring the theme of subordination and the role of women within the traditions of the Kasunanan Surakarta Palace. The focus centers on the practice of nyêntir and the dhodhok movement, historically performed by female abdidalêm, whose roles are often marginalized both socially and performatively. The creative process is developed through three reflective phases: Re-Visiting , which examines the historical and cultural meanings of dhodhok; Re-Questioning, which reconsiders the position of women within patriarchal social structures; and Re-Interpreting, which transforms the symbol of the subordinate body into an empowered expression through contemporary movement language. This work goes beyond physical aesthetics to offer a social critique of symbolic domination within traditional cultural systems. Through movement, spatial composition, and bodily relations, the piece constructs a visual narrative of empowered humility. “Sub-Ordinat” was performed during the opening of World Dance Day at the Indonesian Institute of the Arts (ISI) Surakarta as part of a collaborative presentation alongside Nuryanto’s work, Ramayana Kontemporer. This collaboration served as a space for dialogue between tradition and innovation, while also reinforcing the importance of critical awareness toward women’s roles and contributions in performing arts.